2016
DOI: 10.1101/043208
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic adaptations in a range expanding arthropod

Abstract: Despite an increasing number of studies documenting life-history evolution during range expansions or shifts, we lack a mechanistic understanding of the underlying physiological processes. In this explorative study, we used a metabolomics approach to study physiological changes associated with the recent range expansion of the two-spotted spider mite (Tetranychus urticae). Mite populations were sampled along a latitudinal gradient from range core to edge and reared under benign common garden conditions for two… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
(21 reference statements)
0
8
2
Order By: Relevance
“…Those at the range edge display substantial upregulation genes involved with metabolism and activity (Rollins et al 2015), which contrasts with findings from metabolomics of invasive spider mites (Tetranychus urticae) that have undergone a range expansion (Van Petegem et al 2016b). Individuals from the expanding range edge potentially downregulate metabolic pathways associated with protein synthesis and also show differential use of amino acids to those individuals from the range core (Van Petegem et al 2016b). These recent findings demonstrate the complexity of evolutionary processes at range edges that remains to be understood, and highlights the importance of integrating advances in metabolomics and epigenetic technologies.…”
Section: Future Directionscontrasting
confidence: 48%
See 3 more Smart Citations
“…Those at the range edge display substantial upregulation genes involved with metabolism and activity (Rollins et al 2015), which contrasts with findings from metabolomics of invasive spider mites (Tetranychus urticae) that have undergone a range expansion (Van Petegem et al 2016b). Individuals from the expanding range edge potentially downregulate metabolic pathways associated with protein synthesis and also show differential use of amino acids to those individuals from the range core (Van Petegem et al 2016b). These recent findings demonstrate the complexity of evolutionary processes at range edges that remains to be understood, and highlights the importance of integrating advances in metabolomics and epigenetic technologies.…”
Section: Future Directionscontrasting
confidence: 48%
“…A recent genetic study on invasive cane toads has found differential expression of genes involved in metabolism and immune function between individuals from range edge and range core populations (Rollins et al 2015). Those at the range edge display substantial upregulation genes involved with metabolism and activity (Rollins et al 2015), which contrasts with findings from metabolomics of invasive spider mites (Tetranychus urticae) that have undergone a range expansion (Van Petegem et al 2016b). Individuals from the expanding range edge potentially downregulate metabolic pathways associated with protein synthesis and also show differential use of amino acids to those individuals from the range core (Van Petegem et al 2016b).…”
Section: Future Directionscontrasting
confidence: 47%
See 2 more Smart Citations
“…Metabolic profile changes in response to stress exposure, and their (putative) functional roles, have been extensively documented, especially in arthropods (Bundy et al, 2008; Steinberg, 2012; Teets and Denlinger, 2013). In contrast, metabolite differences between dispersers and residents even in interaction with the environment- are surprisingly understudied, compared to other phenotypic differences (Cote et al, 2017; Ronce and Clobert, 2012; but see Tung et al, 2018; Van Petegem et al, 2016).…”
Section: Introductionmentioning
confidence: 98%